2019
DOI: 10.3390/en12173307
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Thermodynamic Models for Simulation and Optimisation of Organic Rankine Cycles

Abstract: Equations of state (EOSs) form the base of every thermodynamic model used in the design of industrial processes, but little work has been done to evaluate these in the context of such models. This work evaluates 13 EOSs for their accuracy, computational time and robustness when used in an in-house optimisation program that finds the maximum power output of an organic Rankine cycle. The EOSs represent popular choices in the industry, such as the simple cubic EOSs, and more complex EOSs such as the ones based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…[116], it was shown that the van-der-Waals equation for non-ideal gases corresponds in LGM to the approach of an average field. All other constructions for phenomenological equations of a state are derived in the same style [103,104,117,118]; this leads to the obvious contradiction when modeling SCF processes: various phenomenological equations of a state reflect the non-ideality of a reactionary system, whereas the equations for kinetic models do not reflect the non-ideality of systems.…”
Section: The Equations Of a State For Non-ideal Systems And Their Con...mentioning
confidence: 99%
See 1 more Smart Citation
“…[116], it was shown that the van-der-Waals equation for non-ideal gases corresponds in LGM to the approach of an average field. All other constructions for phenomenological equations of a state are derived in the same style [103,104,117,118]; this leads to the obvious contradiction when modeling SCF processes: various phenomenological equations of a state reflect the non-ideality of a reactionary system, whereas the equations for kinetic models do not reflect the non-ideality of systems.…”
Section: The Equations Of a State For Non-ideal Systems And Their Con...mentioning
confidence: 99%
“…On the other hand, different equations of states can be used in one work. In [103] 14 equations of states were used; similarly, 13 equations of states were considered in [104].…”
Section: Introductionmentioning
confidence: 99%
“…Recent papers [1][2][3][4] prove that this topic is a well-studied one by the analysis of thermodynamic models for the simulation and optimization of power systems [1,2], as well as energy and exergy analysis of waste heat recovery systems [3,4]. For instance, an assessment with the citation indexing service Web of Science, that provides a comprehensive citation search through multiple databases, gives for "waste heat" a total of 23,717 references within its core collection over the period 1950-2017, of which 313 are highly cited.…”
Section: Introductionmentioning
confidence: 99%